Environmental voluntary agreements: A new model of co-operation between public and economic actors - Giulia Pesaro (Fondazione Eni Enrico Mattei (FEEM), 2001)
The diffusion of voluntary agreements can be considered as the result of the innovation of environmental policies based on a new style of interaction between public and private actors. As the environmental problems complexity increases, an evolution of interaction model occurs.The literature on environmental policy innovation shows in a clear way that the use of voluntary agreements and their real capability to produce relevant effects are strictly linked to the innovation paths of environmental policies, policy styles and policy networks. In this paper we will focus our attention on the evolution of the model of interaction between public and economic actors as the key element to evaluate voluntary agreements' effectiveness in reaching policy targets.
Keywords: 330; Environmental policy instruments; voluntary agreements; Selbstverpflichtung; Umweltpolitik; EU-Staaten